Structure and microstructure of PbTiO3 thin films obtained from hybrid chemical method - Ignacio, C.; Soares, A. R.; Yukimitu, K.; Moraes, João Carlos Silos [UNESP]; Malmonge, J. A.; Nunes, V. B.; Zanette, S. I.; Araujo, E. B. (Elsevier B.V., 2003)
PbTiO3 thin films were deposited on Si(100) via hybrid chemical method and crystallized between 400 and 700 degreesC to study the effect of the crystallization kinetics on structure and microstructure of these materials. X-ray diffraction (XRD) technique was used to study the structure of the crystallized films. In the temperature range investigated, the lattice strain (c/a) presented a maximum value (c/a = 1.056) for film crystallized at 600 degreesC for I h. Atomic force microscopy (AFM) was used in investigation of the microstructure of the films. The rms roughness of the films linearly increases with temperature and ranged from 1.25 to 9.04 nm while the grain sizes ranged from 130.6 to 213.6 nm. Greater grain size was observed for film crystallized at 600 degreesC for 1 h. (C) 2002 Elsevier B.V. S.A. All rights reserved.
Keywords: crystallization; ferroelectric; thin films